1992
DOI: 10.1002/pd.1970120503
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic results from the U.S. collaborative study on CVS

Abstract: Cytogenetic data are presented for 11,473 chorionic villus sampling (CVS) procedures from nine centres in the U.S. NICHD collaborative study. A successful cytogenetic diagnosis was obtained in 99.7 per cent of cases, with data obtained from the direct method only (26 per cent), culture method only (42 per cent), or a combination of both (32 per cent). A total of 1.1 per cent of patients had a second CVS or amniocentesis procedure for reasons related to the cytogenetic diagnostic procedure, including laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(241 citation statements)
references
References 29 publications
13
223
3
Order By: Relevance
“…When mosaicism occurs during the cleavage state, for example, the mosaicism will be more pronounced (a greater percentage of the total embryo involved) than if the mosaicism occurs later in development. This suggestion is supported by a comparison of the rates of mosaicism seen in prenatal diagnosis (1-2 %) versus the broad range (50-90 %) of mosaicism seen in cleavage stage embryos [10,36].…”
Section: Technological Failurementioning
confidence: 87%
“…When mosaicism occurs during the cleavage state, for example, the mosaicism will be more pronounced (a greater percentage of the total embryo involved) than if the mosaicism occurs later in development. This suggestion is supported by a comparison of the rates of mosaicism seen in prenatal diagnosis (1-2 %) versus the broad range (50-90 %) of mosaicism seen in cleavage stage embryos [10,36].…”
Section: Technological Failurementioning
confidence: 87%
“…The major advantage of CVS over amniocentesis is that it can be performed at a much earlier stage of pregnancy and entails a minor physical and probably smaller emotional risk to the woman who receives a positive result and requests a TOP. However, compared with amniocentesis, when CVS is used for a fetal karyotype there is a greater likelihood of needing a repeat test because of unclear results, mainly mosaicisms, which are detected in one case out of 50 [Ledbetter et al, 1992;Baffero et al, 2012].…”
Section: Methods Of Prenatal Diagnosismentioning
confidence: 99%
“…10 Large, multicenter studies have determined that the frequency of mosaicism in either direct or cultured analysis of CVS tissue to be 1-2%. 8,11 When trisomy mosaicism was detected by CVS in these studies, in ~80% of the cases the chromosome abnormalities were confined to the placenta with normal fetal chromosome constitution. Furthermore, these studies indicated that if the chromosome abnormality were detected by the direct method and therefore confined to the cytotrophoblast tissue and not detected in the cultured chorionic villi, then the chromosome abnormality was never confirmed in fetal tissues (i.e., amniocentesis, cord blood).…”
Section: Brief Reportmentioning
confidence: 99%